Metodologias ativas de ensino aprendizagem no curso de graduação em enfermagem: a percepção do estudante - Ferreira, Anne Laura Costa (2013)
The society transformations and demands for health training are improving and require a professional who answers the real needs of local population, which is grounded in National Curriculum Guidelines for graduation courses in health area (2001 ). The pedagogical process requires teaching-learning methodologies that fit this context and prepare the learner for the full realization of practice. The active methodologies as motivators of that process which start from the experienced practice and from problem situations that hatch with daily reflection, becomes in use. Based on these considerations the aim of this research was to analyze the understanding of the nursing course student about the use of active teachinglearning methods in graduation. This research was approached through an educational type case study and qualitative analysis. Through the results it could be noticed that even with the structure of the disciplinary curriculum and the isolated initiative of an active methodology insertion, the students approved the method and pointed out as a better form of knowledge construction which favors the teacherstudent relationship and emphasizes independence and freedom acquired in the formation process of the learner. It concludes that the student seen as an author of the teaching process and the teacher as a mediator of it, translate a great advance in education quality and student’s maturation.